PENGARUH ION LOGAM TERHADAP AKTIVITAS LIPASE DARI BAKTERI AIR BEKAS GALIAN TAMBANG DI SAMARINDA - Haeruddin, Haeruddin; Astuti, Winni; Pratiwi, Djihan Ryn (PROSIDING SEMINAR KIMIA, 2023)
Addition of metal ions on lipase activity has been done. The aim of this research is to find out the effect of metal ions on lipase activity from water bacterial post mining in Samarinda. Lipase activity was determined based on the Titrimetric method with olive oil as a substrate. The result showed lipase activity from water bacterial post mining without the addition of metal ions is 1,0 U/mL and with the addition of metal ions Mg2+, K+, Fe3+, Ca2+, dan Ba2+their respective lipase activities is 0,6 U/mL, 0,7 U/mL, 1,9 U/mL, 1,4 U/mL dan 0,8 U/mL. The conclusion that can be drawn that is metal ions K+, Mg2+ and Ba2+ inhibit lipase activity with a relative activity each at 70; 60 dan 80% while Ca2+ increase lipase activity with a relative activity at 140% and Fe3+ causes denatured lipase with a relative activity at 190%. Keywords: Bacteria, Lipase, Metal Affect